Prognostic Value of Baseline Total Metabolic Tumor Volume Measured on FDG PET in Patients With Richter Syndrome. (February 2020) - Pontoizeau, Clémence; Girard, Antoine; Mesbah, Habiba; Haumont, Laure-Anne; Devillers, Anne; Tempescul, Adrian; Salaün, Pierre-Yves; Lamy, Thierry; Le Jeune, Florence; Palard-Novello, Xavier
Abstract : Purpose: We evaluated the prognostic value of baseline total metabolic tumor volume (TMTV) measured using pretreatment FDG PET for patients with transformation of chronic lymphocytic leukemia (CLL) into diffuse large B-cell lymphoma (DLBCL). Methods: A total of 28 patients with transformation of CLL into DLBCL who had undergone FDG PET before treatment were retrospectively reviewed. Univariate and multivariate analysis of conventional clinicopathologic variables (sex, age, World Health Organization performance status score, International Prognostic Index score, Binet stage, lactate dehydrogenase serum level [LDH], platelet count, presence or not of prior therapies for CLL, the time from CLL to Richter syndrome, Ann Arbor stage, Bulky or not) and metabolic parameters (SUVmax, SUVmean, TMTV, and total lesion glycolysis) at the time of the transformation of CLL into DLBCL were tested for overall survival (OS). Results: Of the 28 patients, 14 patients (50%) died during the follow-up period. Low platelet count, World Health Organization performance status score >1, high LDH, and high TMTV were found to be significant prognostic factors for OS on univariate analysis. The 5-year estimates of OS were 63% in the low metabolic burden group (TMTV ⩽1200 cm 3 ) and 0% in the high metabolic burden group (TMTV >1200 cm 3 ). Multivariate analysis revealed that only high LDH was a significant predictor after adjustment for other variables of OS. Conclusions: TMTV extracted from FDG PET at the time of the transformation of CLL into DLBCL is a predictor of OS.